2014
DOI: 10.1007/s11427-014-4637-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of the N-methyl-d-aspartate receptor in the proliferation of adult hippocampal neural stem and precursor cells

Abstract: New neurons are continuously generated from resident pools of neural stem and precursor cells (NSPCs) in the adult brain. There are multiple pathways through which adult neurogenesis is regulated, and here we review the role of the N-methyl-D-aspartate receptor (NMDAR) in regulating the proliferation of NSPCs in the adult hippocampus. Hippocampal-dependent learning tasks, enriched environments, running, and activity-dependent synaptic plasticity, all potently up-regulate hippocampal NSPC proliferation. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 77 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Research on rodent has begun to elucidate the molecular and cellular mechanisms activated by voluntary running that are likely to sustain the positive effect of physical exercise on cognition and memory, which is mediated, at least in part, by increased angiogenesis, synaptogenesis and hippocampal neurogenesis. In the hippocampus, structural modifications of dendritic morphology are thought to play a major role in neuronal functioning [ 223 ]; in this context, adult neurogenesis in the DG provides additional plasticity to the hippocampal circuitry [ 224 , 225 ]. The increase of neural stem/progenitor cells in the DG neurogenic niche, together with the increase of synaptic plasticity in existing neurons, may be essential mediators of the improvement of hippocampus-dependent memory exerted by physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Research on rodent has begun to elucidate the molecular and cellular mechanisms activated by voluntary running that are likely to sustain the positive effect of physical exercise on cognition and memory, which is mediated, at least in part, by increased angiogenesis, synaptogenesis and hippocampal neurogenesis. In the hippocampus, structural modifications of dendritic morphology are thought to play a major role in neuronal functioning [ 223 ]; in this context, adult neurogenesis in the DG provides additional plasticity to the hippocampal circuitry [ 224 , 225 ]. The increase of neural stem/progenitor cells in the DG neurogenic niche, together with the increase of synaptic plasticity in existing neurons, may be essential mediators of the improvement of hippocampus-dependent memory exerted by physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Both systemic administration of the competitive NMDAR antagonist CGP43487 and MK-801 treatments induced a twofold increase in the number of [ 3 H]thymidine-labeled cells in the granule cell layer compared with the control group (6). In contrast, treatment with NMDA, the major agonist of the NMDAR, resulted in a significant reduction in proliferation in the granule cell layer (6,41). In this study, we found that the proliferation ability and cell viability of bone marrow MSCs of the intrauterine hypoxia group were significantly reduced compared with those of the control group in vitro.…”
Section: Discussionmentioning
confidence: 54%
“…The results of our previous study also revealed NMDA receptor expression in MSCs extracted from mouse bone marrow (21). Studies also revealed that direct modulation of NMDARs alters hippocampal neural stem and precursor cell proliferation in the adult hippocampus (41). Both systemic administration of the competitive NMDAR antagonist CGP43487 and MK-801 treatments induced a twofold increase in the number of [ 3 H]thymidine-labeled cells in the granule cell layer compared with the control group (6).…”
Section: Discussionmentioning
confidence: 68%
“…In our review, we discuss the role of the N-methyl-D-aspartate receptor (NMDAR) in regulating the pools of neural stem and precursor cells in the hippocampus, which play such a crucial part in regulating the neurogenesis that underpins hippocampal learning and memory. Enhancement of this neurogenic process may be potentially used to ameliorate the effects of dementia [6]. In collaboration with Professor Jürgen Götz's laboratory (QBI), the He laboratory further explores processes underlying the major form of dementia, Alzheimer's disease (AD).…”
mentioning
confidence: 99%